Antiretroviral-naïve HIV-infected patients had lower bone formation markers than HIV-uninfected adults. Issue 8 (2nd August 2020) - Wattanachanya, Lalita; Jantrapakde, Jureeporn; Avihingsanon, Anchalee; Ramautarsing, Reshmie; Kerr, Stephen; Trachunthong, Deondara; Pussadee, Kanitta; Teeratakulpisarn, Nipat; Jadwattanakul, Tanate; Chaiwatanarat, Tawatchai; Buranasupkajorn, Patinut; Phanuphak, Nittaya; et al.
ABSTRACT: There are limited studies regarding bone health among people living with HIV (PLHIV) in Asia. We compared bone mineral density (BMD), serum 25-hydroxyvitamin D (25(OH)D) status and bone turnover markers (serum procollagen type1 N-terminal propeptide (P1NP), osteocalcin (OC) and C-terminal cross-linking telopeptide of type1 collagen) among 302 antiretroviral therapy (ART) naive PLHIV compared to 269 HIV-uninfected controls from Thailand. People aged ≥30 years, with and without HIV infection (free of diabetes, hypertension, and active opportunistic infection) were enrolled. BMD at the lumbar spine, total hip, and femoral neck were measured using Hologic DXA at baseline and at 5 years. We analyzed BMD, serum 25(OH)D levels, and bone turnover markers at the patients' baseline visit. PLHIV were 1.5 years younger and had lower BMI. PLHIV had higher mean serum 25(OH)D level and similar BMD to the controls. Interestingly, PLHIV had significantly lower bone formation (serum P1NP and OC), particularly those with low CD4 count. Only a few participants had low bone mass. ARV naïve middle-aged PLHIV did not have lower BMD or lower vitamin D levels compared to the controls. However, PLHIV had lower bone formation markers, particularly those with low CD4 count. This finding supports the benefit of early ART.